Psychometric Properties of the Liebowitz Social Anxiety Scale in Peruvian University Students - Franco-Jimenez, Rulman Andrei (2020)
The aim of the study was to examine the psychometric properties of the Liebowitz Social Anxiety Scale (LSAS), analyzing factor structure and internal consistency. The sample was composed of 549 undergraduate students of a Peruvian public university. Confirmatory factor analysis was used in order to compare models of two, three, four, five and six factors. The best model fit indices were found in the five-factor model proposed by Caballo, Salazar, Arias, Hofmann & Curtis (2019), χ² = 319.43, CFI = .991, RMSEA = .043, TLI = .990, SRMR = .051. Also, the internal consistency of the five factors was analyzed using omega coefficient which ranged from .81 to .62. In conclusion, LSAS presents appropriate psychometric properties and the results support the five-factor structure.